Diagnosis of malaria parasites plasmodium spp. in endemic areas: current strategies for an ancient disease - Gitta, Brian; Kilian, Nicole (Bioessays, 2020)
Various diagnostic methods are available to detect the six human pathogenic Plasmodium species that replicate within host erythrocytes and cause different types of malaria. Every currently available ...
First published: 12 December 2019
Gesehen am 14.01.2021